Morphological characterization of hydrocolloids using scanning electron microscopy and evaluation of their effects in a model system of low-calorie fruit jelly - Monteiro, Reginaldo de Souza; Postgraduate Program in Health and Nutrition, Federal University of Ouro Preto, Campus Morro do Cruzeiro, Zip code: 35400000 Ouro Preto, Minas Gerais, Brazil (2020)
It is important to understand the stability of the formed gels and the factors that affect the behavior of these agents in a complex system to impart desirable properties to a new product. The purpose of this paper was to evaluate the morphological structure of gelling agents, LM-pectin, kappa-carrageenan and guar gum and to study the effects of these gelling agents in low-calorie fruit jelly model systems. Scanning electron microscopy (SEM) analysis allowed us to recognize the morphology of the gelling agents of interest, and showed that only the powdered samples of LM-pectin and kappa-carrageenan presented structures that collaborate for the process of gelling. Based on all the information gathered through the analysis of low-calorie fruit jelly modeling systems using the gelling agents studied, we suggest that the best combinations among the formulations tested were those containing concentrations higher or equal than 75% LM-pectin.